(untitled) (International Journal of Engineering and Computer Science, 2015)
The recent influx of glazing materials being used as curtain walls in Ghana has resulted in the increase use of energy to provide thermally comfortable interior spaces for occupant comfort. The ‘glass box’ phenomenon in Ghana has arisen due to contemporary architecture. The climate of Ghana (warm humid) makes it almost impossible for these multi-storey glass boxes to be ventilated naturally throughout the year. The current study was aimed at finding means of significantly reducing the cooling loads of these multi-storey office buildings whilst ensuring thermal comfort. Four high rise office buildings in Accra were selected for the study. Several parameters ranging from efficient glazing, thermal mass, façade insulation, night ventilation etc were probed into towards the reduction of cooling loads. The study revealed amongst others that reduced light loads of 2W/m2 considerably decreased cooling loads in all the buildings. Efficient glazing with low solar heat gain coefficient also cut down on cooling loads by as much as 27%. Additionally, it was realized that external shading could reduce cooling loads and therefore architects must make a conscious effort to provide same when designing these buildings.